2021
DOI: 10.4018/ijkm.2021040105
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Intellectual Capital Bottom-Line in Professional Service Firms

Abstract: The contribution of professional service firms (PSFs) has always been phenomenal in the knowledge economies. Given the ever-increasing focus on achieving knowledge-based trans-formations, the effectiveness of these firms is highly attributed to the knowledge capabilities embedded in their staff and how efficiently they are utilized in firm's optimal benefit. In view of growing services sector, it is vital for these firms to implement high performance work practices (HPWPs) so as to maintain high-quality servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Much of the researchers consider the importance of evaluating intellectual capital by a system of balanced scores, in particular (Kaplan R. S., Norton D. P. (1996). Rehman J., Hawryszkiewycz I., Sohaib O., Namisango F. (2021) the importance of implementing measures that enhance skills, motivation and capabilities is empirically proved, which provides growth of intellectual capital and competitive advantage. Gupta, K., Raman, T. V. (2021) used the modified value-added intellectual coefficient (VAIC) as an opportunity to measure intellectual capital and return on assets to measure the financial performance of firms.…”
Section: Methodsmentioning
confidence: 99%
“…Much of the researchers consider the importance of evaluating intellectual capital by a system of balanced scores, in particular (Kaplan R. S., Norton D. P. (1996). Rehman J., Hawryszkiewycz I., Sohaib O., Namisango F. (2021) the importance of implementing measures that enhance skills, motivation and capabilities is empirically proved, which provides growth of intellectual capital and competitive advantage. Gupta, K., Raman, T. V. (2021) used the modified value-added intellectual coefficient (VAIC) as an opportunity to measure intellectual capital and return on assets to measure the financial performance of firms.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature on strategic human resource management work practices have been discussed extensively in the context of high-performance work systems, generally in relation to the diffusion of Japanese-style organisational work practices in the US and Europe. Highperformance organisational practices and arrangements are seen as enhancing a firm's capacity for making incremental improvements to efficiency and quality (Arundel et al 2007;Rehman et al 2021). These practices tend to centre on increasing employee involvement in problem solving and decision-making.…”
Section: Organisational Work Practicesmentioning
confidence: 99%
“…Although knowledge-intensive organisations (KIOs) are main players in the economy (Liu et al, 2020), for their significant contribution to the global economy's growth (National Science Board National Science Foundation [NSB/NSF], 2022), their strategic management is a challenge in the academic area, as well as in the corporate world (Rehman et al, 2020). Rehman et al (2021) indicate that their study has been really limited. For Murphy and Seriki (2021), little attention has been paid to study these companies, which is confirmed by Bandarian (2020), who affirms that more studies are required to explain the construction of competitive advantage (CA) in those businesses, mainly in emerging markets (Mathew et al, 2021).…”
Section: Introductionmentioning
confidence: 99%